Prasugrel achieves greater inhibition of platelet aggregation and a lower rate of non-responders compared with clopidogrel in aspirin-treated patients with stable coronary artery disease - Jernberg, Tomas; Payne, Christopher D.; Winters, Kenneth J.; Darstein, Christelle; Brandt, John T.; Jakubowski, Joseph A.; Naganuma, Hideo; Siegbahn, Agneta; Wallentin, Lars (European heart journal, 2006)
This study was designed to compare the degree of inhibition of platelet aggregation (IPA) of prasugrel with that of clopidogrel in stable aspirin-treated patients with coronary artery disease (CAD). Subjects (n=101) were randomly assigned to the following loading dose (LD) (day 1)/maintenance dose (MD) (days 2-28) combinations: prasugrel, 40 mg/5 mg; 40 mg/7.5 mg; 60 mg/10 mg; 60 mg/15 mg; or clopidogrel, 300 mg/75 mg. Turbidometric platelet aggregation was measured at multiple timepoints during the study. At 4 h after dosing, with 20 microM ADP, both prasugrel LDs achieved significantly higher mean IPA levels (60.6% and 68.4 vs. 30.0%, respectively; all P<0.0001) and lower percentage (3 vs. 52%, P<0.0001) of pharmacodynamic non-responders (defined as IPA <20%) than clopidogrel. Prasugrel 10 and 15 mg MDs achieved consistently higher mean IPA than clopidogrel 75 mg at day 28 (all P<0.0001). At pre-MD on day 28, there were no non-responders in the 10 and 15 mg prasugrel group, compared with 45% in the clopidogrel group (P=0.0007). In this population, prasugrel (40-60 mg LD and 10-15 mg MD) achieves greater IPA and a lower proportion of pharmacodynamic non-responders compared with the approved clopidogrel dosing.